MAPPING SUSTAINABLE SUPPLY CHAIN MANAGEMENT IN HOSPITALITY INDUSTRY – A BIBLIOMETRIC ANALYSIS - Susanti, Christina; Lusy (ITB AAS Indonesia Surakarta, 2025)
As a vital part of the tourism sector, the hospitality industry plays a significant economic role but also contributes considerably to environmental degradation. Sustainable Supply Chain Management (SSCM) has emerged as a strategic approach to address these ecological impacts while improving operational and economic performance. This study presents a comprehensive bibliometric analysis of the SSCM literature within the hospitality industry from 2015 to 2025, utilizing data extracted from the Scopus database. Using RStudio (Biblioshiny), VOSviewer, and Scopus Analyze. This research identifies publication trends, key contributing authors, prominent journals, countries, and the co-occurrence of keywords to map the intellectual structure of the field. A total of 95 articles were analyzed, revealing an upward trend in SSCM research, particularly following the COVID-19 pandemic. The findings indicate that the field is multidisciplinary, with significant contributions from business, social sciences, and environmental studies. China and Spain are the leading contributor countries, while the most frequently used keywords include